Inside Cover: Effect of tissue staining in quantitative phase imaging (J. Biophotonics 8/2018). Issue 8 (8th August 2018) - Ban, Sungbea; Min, Eunjung; Ahn, Yujin; Popescu, Gabriel; Jung, Woonggyu
Abstract : The effect of tissue staining in wide‐field quantitative phase imaging is negligible when using a light source out of the absorption spectrum. Further details can be found in the article by Sungbea Ban, Eunjung Min, Yujin Ahn, Gabriel Popescu, and Woonggyu Jung (e201700402 ) Abstract : The effect of tissue staining in wide‐field quantitative phase imaging is negligible when using a light source out of the absorption spectrum. Further details can be found in the article by Sungbea Ban, Eunjung Min, Yujin Ahn, Gabriel Popescu, and Woonggyu Jung (e201700402 )